การใช้สื่อมวลชนสร้างชื่อเสียงของนักการเมือง - อาภา อนันตกูล (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this qualitative research was to find out how politicians used mass media to create a name for themselves. The researcher selected Mrs. Paveena Hongsakul and Dr. Bhichit Rattakul as case studies. The building of reputations through daily newspapers and television news from 1995-1998 was examined. The researcher observed the practice of their name-making through mass media. Interviews with both Mrs. Paveena and Dr. Bhichit, their teams of supporters, other politicians and mass media were conducted in depth. The result of the study shows that there are three ways politicians use mass media to create their reputation. They are : 1) to present their activities and inform mass media of their movements 2) to form good relationships with the mass media and 3) to form private teams of supporters with media experience past and present. Moreover, it is found that the significant factors for politicians to create celebrity are their background, namely family, educational background, performance before entering political circles, political life development and personality trait; activities and the degree of their relationships with the mass media.